(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article, discusses the vital role of planning in effective teaching and learning, particularly focusing on syllabus lesson plans. It explains that a syllabus serves as a structured guide outlining course objectives, content, assessments, and expectations, helping bridge curriculum and classroom instruction. The article emphasizes the importance of analyzing and adapting the syllabus based on context and resources. Furthermore, it elaborates on lesson planning asa detailed, daily strategy for achieving learning outcomes, ensuring classroom time is used effectively. The comonents of a lesson plan—objectives, resources, activities, assessment, and reflection—are thoroughly outlined. The article concludes that structured planning enhances teaching quality, student engagement, and curriculum alignment across all educational levels.